Analisis Fundamentaldan Penilaian Saham Dengan Mengunakan Metode Dividen Discount Model Terhadap Pengambilan Keputusan Investasi (Studi pada Perusahaan Otomotif yang terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Sariningsih, Eka; Puspita, Indah Lia; Azzis, Muhammad Fahmi (Universitas Malahayati, 2025)
This study aims to assess the fairness of stock prices in three automotive companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, namely PT Astra International Tbk (ASII), PT Selamat Sempurna Tbk (SMSM), also PT Multistrada Arah Sarana Tbk (MASA). The method used in this study is the Dividend Discount Model (DDM), which is one of the fundamental analysis approaches to calculate the intrinsic value of shares based on future dividend projections. The analysis was carried out by calculating financial indicators such as Dividend Per Share (DPS), dividend growth rate (g) also required rate of return (k). The results of the study showed two of the three companies, namely ASII also SMSM, had a higher intrinsic value than the market price (undervalued), so it was recommended to buy them. Meanwhile, MASA shares cannot be valued using the DDM method because they did not distribute dividends consistently during the observation period.